Image Classification On Ex-Mining Land Area Using Echo Classifier - Baharuddin, Salmah (2003)
The purpose of this study is to map the landcover ofa large and complex surface of an ex-mining land area using remote sensing technology. Remote sensing imagery has proven useful to generate landcover and it is timely, potentially less expensive than conventional ground methods. Study goals included evaluation of various classification algorithms, deriving a landcover map of the ex-mining land using satellite image and collection of ground truth points in order to perform a more quantitative analysis and accuracy assessment of the methods used.